Baby-friendly hospital practices are associated with duration of full breastfeeding in primiparous but not multiparous Iranian women - Zarshenas, Mahnaz; Zhao, Yun; Binns, Colin; Scott, Jane (Wiley-Blackwell Publishing, 2018)
© 2018 John Wiley & Sons Ltd. There is evidence that the Baby-Friendly Hospital Initiative (BFHI) results in improved breastfeeding outcomes in Western countries, but little is known of its impact in Middle-Eastern countries. This study investigated the impact of BFHI practices on duration of full breastfeeding in a cohort of 700 Iranian mothers recruited between June 2014 and March 2015 from maternity hospitals in Shiraz and followed-up prospectively for 6 months. At baseline, mothers self-reported exposure to 7 of the BFHI Ten Steps to Successful Breastfeeding (Steps 3 to 9). Data on breastfeeding outcomes were collected at baseline, 1, 3, 4, and 6 months postpartum. Cox regression analysis was conducted to determine the impact of individual and cumulative BFHI Steps on the duration of full breastfeeding, defined as the number of weeks since discharge that an infant received only breast milk and no complementary formula or food. Mothers reported experiencing on average 3.9 (SD 1.13, range 1 to 7) Steps, and only 28% of infants were fully breastfed at 6 months. There was a protective inverse relationship for primiparous (p for trend = .022) but not multiparous mothers (p for trend = .069), between the number of Steps a woman was exposed to and the likelihood of her discontinuing full breastfeeding within 6 months postpartum. Greater exposure to BFHI practices potentially could increase primiparous mothers' chances of fully breastfeeding to 6 months. Continual monitoring of the BFHI Steps and repeated education of healthcare staff are required to ensure that Iranian mothers receive adequate breastfeeding support.